2017
DOI: 10.17116/terarkh2017891114-20
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subpopulations, levels of interferon, and expression of their receptors in patients with chronic hepatitis B and C: Correlation with the species of viruses and the degree of liver fibrosis

Abstract: Several new clinical and laboratory trends were identified and the nature and extent of previously described hematological and immunological changes were clarified in CHC or CHB patients with various degrees of LF. Some indicators may be used as additional criteria for the prognosis of the above forms of hepatitis, and a number of newly described facts suggest that it is necessary to revise the protective/phlogogenic value of types I, II, and III IFNs in chronic viral hepatitis C and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Many studies have shown that carriers of hepatitis B surface antigen (HBsAg) have higher risk of HCC compared to HBsAg negative cases 4 . Several other studies showed that hepatitis B and C infections may increase the risk of lymphoid malignancies 5 , pancreatic cancer 6 , liver fibrosis 7 and chronic kidney disease 8 . Moreover, studies have shown that hepatitis C virus (HCV) is present not only in hepatocytes, but also in patients' plasma and serum.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that carriers of hepatitis B surface antigen (HBsAg) have higher risk of HCC compared to HBsAg negative cases 4 . Several other studies showed that hepatitis B and C infections may increase the risk of lymphoid malignancies 5 , pancreatic cancer 6 , liver fibrosis 7 and chronic kidney disease 8 . Moreover, studies have shown that hepatitis C virus (HCV) is present not only in hepatocytes, but also in patients' plasma and serum.…”
Section: Introductionmentioning
confidence: 99%